2021
DOI: 10.3389/fnhum.2021.734179
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Interconnections Between Statistical Learning and Dyslexia: A Review of Recent Empirical Studies

Abstract: One important aspect of human cognition involves the learning of structured information encountered in our environment, a phenomenon known as statistical learning. A growing body of research suggests that learning to read print is partially guided by learning the statistical contingencies existing between the letters within a word, and also between the letters and sounds to which the letters refer. Research also suggests that impairments to statistical learning ability may at least partially explain the diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 138 publications
1
3
0
Order By: Relevance
“…First, we zoomed into the incremental temporal trajectory of pseudoword learning and found slower establishment of cortical tracking along with poor explicit recognition in dyslexic readers (Chapter 3). This aligns with prior work indicating a domain-general statistical learning difficulty in dyslexia (Schmalz et al, 2017;Singh & Conway, 2021), characterized by reduced sensitivity to various statistical regularities embedded in the language hierarchy, such as phonotactic probabilities (Bonte et al, 2007;Noordenbos et al, 2013) and artificial grammar (Pothos & Kirk, 2004;Van Witteloostuijn, Boersma, Wijnen, & Rispens, 2017), and also those in non-linguistic temporal sequences (Howard, Howard, Japikse, & Eden, 2006;Lum, Ullman, & Conti-Ramsden, 2013). However, research thus far rarely addressed the incremental learning gains and the associated changes in the neural activity while this implicit learning process took place.…”
Section: Paradigm Shift and Outlooksupporting
confidence: 81%
“…First, we zoomed into the incremental temporal trajectory of pseudoword learning and found slower establishment of cortical tracking along with poor explicit recognition in dyslexic readers (Chapter 3). This aligns with prior work indicating a domain-general statistical learning difficulty in dyslexia (Schmalz et al, 2017;Singh & Conway, 2021), characterized by reduced sensitivity to various statistical regularities embedded in the language hierarchy, such as phonotactic probabilities (Bonte et al, 2007;Noordenbos et al, 2013) and artificial grammar (Pothos & Kirk, 2004;Van Witteloostuijn, Boersma, Wijnen, & Rispens, 2017), and also those in non-linguistic temporal sequences (Howard, Howard, Japikse, & Eden, 2006;Lum, Ullman, & Conti-Ramsden, 2013). However, research thus far rarely addressed the incremental learning gains and the associated changes in the neural activity while this implicit learning process took place.…”
Section: Paradigm Shift and Outlooksupporting
confidence: 81%
“…Using the random effects model, the researchers showed that individuals with DD performed significantly worse than TD controls in visual AGL. S. Singh and Conway (2021) carried out a systematic review of SL in dyslexia focusing on studies published after the three meta-analytical reviews (Lum et al, 2013;Schmalz et al, 2017;M. van Witteloostuijn et al, 2017).…”
Section: Previous Meta-analysesmentioning
confidence: 99%
“…Hence, CSSL impairments are likely to contribute to language deficits observed in language disorders (Ahufinger, Guerra, Ferinu, Andreu, & Sanz-Torrent, 2021;McGregor et al, 2022). If SL deficits in DD (Lee et al, 2022;Nicolson & Fawcett, 2019;Singh & Conway, 2021) also extend to the word level, we can expect that TD readers will outperform readers with DD during CSSL. If people with DD have problems in learning cross-situational statistical regularities, we can expect their performance to deteriorate as SL challenges increase.…”
Section: The Present Studymentioning
confidence: 99%
“…Due to its essential role in typical language acquisition, SL has received considerable attention within the field of language disorders, among them developmental dyslexia (DD; for reviews, see Arciuli & Conway, 2018; Lee, Cui, & Tong, 2022; Schmalz, Altoè, & Mulatti, 2017; Singh & Conway, 2021). DD is a developmental language disorder characterized by difficulty in acquiring reading, writing, and spelling skills despite adequate educational opportunities.…”
Section: Introductionmentioning
confidence: 99%